What explains the gender differences in the adoption of multiple maize varieties? Empirical evidence from Uganda and Tanzania. (June 2020) - Teklewold, Hailemariam; Adam, Rahma I.; Marenya, Paswel
Highlights: We examine gender gap and factors explaining adoption of a mix of maize varieties. Farmers make adoption decisions jointly and substituting one type over the other. Heterogeneous effects of intra household resource ownership on adoption. Farmers adopt drought tolerant varieties if they experience climate shocks. The results indicated return gaps and composition effects on adoption status. Abstract: Understanding the process that underpins the effective and equitable adoption of modern crop varieties remains an imperative for agricultural development in Africa. This study examines gender differences in adoption rates and determinants of the decision to adopt drought-tolerant (DT) and non-drought-tolerant (ND) maize varieties, based on analysis of maize production data from Tanzania and Uganda. Applying a switching regression with multinomial logit models, we exploit plot level adoption decisions by women and men individually or jointly with in the household, controlling for gender dimension of resource ownership along with other covariates. We find gender differences in the adoption rates for both DT and ND. The results suggest substitution effects noticeable in the decision to use one maize variety rather than another. As the size of the area about which both spouses are jointly owned increases, so does the likelihood that they will adopt DT. Furthermore, DT adoption is also more likely if farmers have experienced frequent climate shocks and dry spells in the past growing seasons. The differences in adoption behavior between men and women jointly or individually are attributable to a combination of the levels and returns of physical- and social-capital factors, as well as to structural issues. One important policy implication of the results is the need for targeted and disaggregated strategies for scaling modern maize varieties, instead of one-size-fits-all approaches.